In vitro fermentation of carbohydrate by breast fed and formula fed infants. Issue 3 (1st March 1997) - Parrett, A M; Edwards, C A
Abstract : Unabsorbed carbohydrates are fermented by colonic bacteria to short chain fatty acids (SCFA) which are rapidly absorbed, salvaging energy and reducing stool output. There are marked differences between the faecal flora and SCFA of breast fed (BF) and formula fed (FF) infants which may be related to the higher incidence of diarrhoea in FF infants. Part of this effect may be caused by a difference in the ability of the microflora to ferment carbohydrate. To test the hypothesis that BF and FF have different fermentation capacities for simple and complex carbohydrates, in vitro cultures of faeces from healthy infants (2-10 weeks; 11 BF, 11 FF) containing glucose, lactose, raftilose (a fructo-oligosaccharide), or soybean polysaccharide were incubated anaerobically. Results were compared with those of adult faecal cultures using the same carbohydrates. Cultures of faeces from BF and FF infants produced comparable amounts of total SCFA in all cultures. These cultures produced less SCFA than those from adult faeces and produced very little SCFA from complex carbohydrate. BF cultures produced more acetic acid than FF in all cultures, whereas FF cultures produced more propionate with sugars and more butyrate with raftilose. Both groups of infants produced less butyrate than adults in all cultures. Thus it is unlikely that a lower ability to ferment carbohydrate is a major cause of increased risk of diarrhoea in FF fed infants but individual SCFA production may be important.